Environmental impact of rejuvenators in asphalt mixtures containing high reclaimed asphalt content. Issue 6 (3rd June 2022) - Muñoz, M.; Haag, R.; Figi, R.; Schreiner, C.; Zaumanis, M.; Cavalli, M. C.; Poulikakos, L. D.; Heeb, N. V.
ABSTRACT: The use of reclaimed asphalt pavement (RAP) is of increasing importance due to fast-growing amounts of demolished road materials. However, reclaimed asphalt can contain relevant amounts of pollutants such as carcinogenic polycyclic aromatic hydrocarbons (PAHs) and toxic metals. In order to improve the mechanical properties of recycled asphalt, rejuvenators are used to reduce the stiffness of the aged binder. These rejuvenators in turn may potentially mobilise pollutants like PAHs and facilitate their leaching to surface and ground waters. The environmental impact of three rejuvenators with good mechanical performance was studied. The environmental impact was assessed by determining metal- and PAH contents in the RAP and in leachates. Chemical analyses showed that rejuvenators did not mobilise PAHs from RAP materials for 2–3 ring PAHs. However, some 4–6 ring PAHs that are relatively less toxic indeed leached more easily from unaged material. Ageing reduced the tendency for PAH leaching, without and with rejuvenator. GRAPHICAL ABSTRACT: UF0001